The Transformational Leadership of School Administrators Affecting Teachers’ Work Motivation under the Pathum Thani Primary Educational Service Area Office 1 - ภู่เทศวิเศษพงศ์ ศิวานันท์; ชวศิริกุลฑล นันทนา; รักษนคร กุลจิรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The purposes of this study were: 1) to examine the transformational leadership of school administrators; 2) to study teacher’s work motivation; 3) to investigate the relationship between transformational leadership of school administrators and teacher’s work motivation; and 4) to examine the transformational leadership of school administrators affecting teacher’s work motivation under Pathum Thani Primary Educational Service Area Office 1. The sample consisted of 333 teachers, determined by using Taro Yamane’s formula. Data were collected through a five-point rating scale questionnaire with an Index of Item-Objective Congruence (IOC) ranging from 0.60 to 1.00 and a reliability coefficient of .987. The statistics used for data analysis included percentage, mean, standard deviation, Pearson’s correlation coefficient, and multiple regression analysis. The research findings revealed that: 1. The transformational leadership of school administrators, both overall and in each aspect, was at the highest level. 2. Teacher’s work motivation, both overall and in each aspect, was at the highest level. 3. The transformational leadership of school administrators has a strong overall positive correlation with teachers’ work motivation (rxy = .812), which is statistically significant at the .01 level. 4. Transformational leadership of school administrators significantly affected teacher’s work motivation at the .01 level of statistical significance. The aspects ranked by standardized and unstandardized multiple regression coefficients from highest to lowest were: 1) inspirational motivation, 2) intellectual stimulation, 3) individualized consideration, and 4) idealized influence, respectively.